2017
DOI: 10.14254/2071-8330.2017/10-1/6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring mechanisms and financial distress of public listed companies in Malaysia

Abstract: Abstract. This study examines the relationships between financial distress and financial ratio (liquidity, leverage, profitability, firm's performance, and dividend) among public listed companies, using the Altman Z-Score to determine the financial distress levels among public listed companies in Malaysia. Five-year data has been collected (2010 to 2014) from the annual financial statements and from Data Stream of public listed companies in Malaysia. The findings indicate significant relationships between liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0
31

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 42 publications
9
41
0
31
Order By: Relevance
“…Research findings by Chan and Chen (1991) showed that financial distress firm have leverage and cash flow problem and thus perform poorly leading to lose in their market value. Similarly, according to Kazemian et al (2017) financial distress, firms are firms that encounter numerous financial problems and have a weak financial performance. Furthermore, Wesa and Otinga (2018) noted that financial distress firms are usually faced with two possible major problems either they are experiencing cash shortage on the asset side or overdue obligation on the liabilities sides of the statement of financial position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research findings by Chan and Chen (1991) showed that financial distress firm have leverage and cash flow problem and thus perform poorly leading to lose in their market value. Similarly, according to Kazemian et al (2017) financial distress, firms are firms that encounter numerous financial problems and have a weak financial performance. Furthermore, Wesa and Otinga (2018) noted that financial distress firms are usually faced with two possible major problems either they are experiencing cash shortage on the asset side or overdue obligation on the liabilities sides of the statement of financial position.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the study will provide firms and the regulators an outlook and idea on what actually determines financial distress of manufacturing firms as this will trigger initiatives and early warning signals that could help avert the probability of corporate financial distress in the sector. According to Kazemian et al (2017) financial distress affects an organization profitability and it operates via its cost implication such as legal cost and administrative cost which is often linked with bankruptcy cost (that is, direct financial cost) and increased cost for supplies and debt (indirect financial distress cost). The implication of these cost (direct and indirect financial distress cost) lowers the market value of firms (Rahman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Crisis management creates more favorable conditions for the company to create a competitive advantage, which allows it to produce products consumed by the market and receive enough money for the further development of the organization (Ganebnykh, 2017). Firms with lower profitability would have a higher possibility of financial distress (Kazemian, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The harmonization of Shariah principles and current business affairs has become a norm in business transactions, as well as provides an overview and appreciation of full compliance with Islamic law (Falaika, 2002 Kazemian, et al, (2017), and Ujah and Brusa (2011). However, the degree and extent of earnings management varies and often depends on the type of economic group or industry (Ujah and Brusa, 2011).…”
Section: Managerial Opportunism and Earnings Managementmentioning
confidence: 99%